Pendampingan Belajar Bahasa Arab melalui Metode Bernyanyi di Musholla Hidayatul Muta’allimat Jember - Asni Furoidah; Mahdia Amalia (INAIFAS Press, 2021)
Learning methods need to be adapted to the age of students as a supporter of success in learning. The easy application of the method allows the improvement of student learning outcomes. The purpose of this study was to increase the spirit of learning Arabic through the singing method at the Musollla Hidayatul Muta'allimat Wuluhan Jember. The approach used in this research is qualitative with data collection through observation and documentation. The results of the research show that the singing method can help increase students' enthusiasm for learning besides that students do not think that Arabic is a difficult subject but a fun and easy lesson.